2016
DOI: 10.5604/20831862.1194125
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin as a novel marker of bone turnover in athletes

Abstract: Sclerostin is a protein secreted by osteocytes that acts as an inhibitor of bone formation. It has been shown that physical activity affects sclerostin concentration and thus bone remodelling. The aim of the study was to evaluate serum concentrations of sclerostin, selected bone turnover markers (PTH, P1NP), 25(OH)D3 and the intake of calcium and vitamin D in physically active versus sedentary men. A total of 59 healthy men aged 17-37 were enrolled in the study (43 athletes and 16 non-athletes). The mean scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
4
10
1
Order By: Relevance
“…Gombos et al [6] found that sclerostin levels increased in a similar group of women as in our study, who underwent a program of walking exercise or resistance exercise, compared to a control group. Similar results were presented by Zagrodna et al [39] who reported that male athletes had significantly higher sclerostin levels than age-matched sedentary men. Also, Lombardi et al [40] investigating sclerostin concentrations in elite athletes, found higher sclerostin levels in males participating in weight-bearing disciplines than in those who participated in nonweight-bearing sports.…”
Section: Prace Oryginalnesupporting
confidence: 90%
“…Gombos et al [6] found that sclerostin levels increased in a similar group of women as in our study, who underwent a program of walking exercise or resistance exercise, compared to a control group. Similar results were presented by Zagrodna et al [39] who reported that male athletes had significantly higher sclerostin levels than age-matched sedentary men. Also, Lombardi et al [40] investigating sclerostin concentrations in elite athletes, found higher sclerostin levels in males participating in weight-bearing disciplines than in those who participated in nonweight-bearing sports.…”
Section: Prace Oryginalnesupporting
confidence: 90%
“…The purpose of this study was therefore to examine the eccentric exercise-induced responses of hormones 8 as well as secreted proteins that are exercise-regulated and have been associated with skeletal muscle regeneration and adaptation, [18][19][20] i.e. GH, insulin-like growth factor binding protein-3 (IGFBP-3), cortisol, prolactin, thyroid-stimulating hormone (TSH), free thyroxine (fT4), irisin, follistatin and sclerostin.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some of these hormones have aroused particular interest because of their potential role in exercise-induced muscle adaptations. [19][20][21][22][23][24] In particular, irisin is a hormone predominantly expressed in human muscle 25,26 and is required for the exercise-induced conversion of white adipose tissue to brown. 18,25 In addition, follistatin is an antagonist of myostatin, the negative regulator of muscle regeneration, 27 while sclerostin is a mechanical loading-regulated protein whose serum levels have been shown to be affected by physical exercise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations